Seasonal predictability of wintertime windstorm climate over the North Atlantic and Europe - Renggli, Dominik (2011)
Abstract iii Zusammenfassung v 1 Introduction 1 1.1 Windstorms in the North Atlantic and European region . . . . . . . . . . . 1 1.1.1 Physical basis . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 1 1.1.2 Impacts of European windstorms . . . . . . . . . . . . . . . . . . . 2 1.2 Seasonal forecasting . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 4 1.2.1 A short history of seasonal forecasting . . . . . . . . . . . . . . . . 4 1.2.2 Physical basis of seasonal forecasting . . . . . . . . . . . . . . . . . 8 1.3 Motivation of the thesis . . . . . . . . . . . . . . . . . . . . . . . . . . . . 17 1.3.1 Seasonal windstorm predictability: a review . . . . . . . . . . . . . 17 1.3.2 Potential use of seasonal windstorm risk predictions . . . . . . . . . 20 1.3.3 Objectives of the thesis . . . . . . . . . . . . . . . . . . . . . . . . . 21 1.3.4 Outlines of the thesis . . . . . . . . . . . . . . . . . . . . . . . . . . 23 2 Data 25 2.1 Reanalysis data . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 25 2.2 Observational data . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 26 2.3 Seasonal prediction model data: DEMETER and ENSEMBLES . . . . . . 27 2.4 Growth factors of extra-tropical cyclones . . . . . . . . . . . . . . . . . . . 30 3 Deﬁnition and identiﬁcation of windstorms 31 3.1 Rational . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 31 3.2 Methods . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 32 3.2.1 Tracking scheme . . . . . . . . . . . . . . . . . . . . . . . . . . . . 32 3.2.2 Storm Severity Index . . . . . . . . . . . . . . . . . . . . . . . . . . 35 3.3 Climatology in reanalysis data . . . . . . . . . . . . . . . . . . . . . . . . . 35 3.4 Sensitivity on tracking parameters . . . . . . . . . . . . . . . . . . . . . . . 38 3.5 Relation to growth factors of cyclones . . . . . . . . . . . . . . . . . . . . . 41 3.6 Conclusions . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 44 4 ...